Pequeños combatientes, de Raquel Robles : Proyecciones ficcionales: de la infancia clandestina a la militancia de H.I.J.O.S. - Basile, Teresa (2017)
Raquel Robles' novel Pequeños combatientes (2013) allows us to explore some of the main challenges faced by the HIJOS organization since its foundation in the mid-90s, a context marked by neoliberalism and Pardon laws passed by the Carlos Menem government. The novel stands as a screen on which the author projects a militant fiction through a girl's voice that connects with her later engagement and practice with HIJOS. This challenge articulates the revolutionary ideals of parents with the humanitarian narrative of Human Rights associations. A return to the past permits to convert the parents' loss into a beginning militancy, the concept of resilience thus helps us to approach the reconversion process of a traumatic scene into a responsible action.